Pendampingan Upaya Pencegahan terhadap Gangguan Penyakit Infeksi Saluran Pernapasan Akut di Kecamatan Selemadeg Timur Kabupaten Tabanan - Ni Made Marwati (Poltekkes Kemenkes Denpasar, 2019)
Assistence in the prevention of acute respiratory infection in the selemadeg subdistrict east tabanan regency. The location of this community service was within the working area of East Selemadeg 1 Public Health Centre in Selemadeg East district, Tabanan regency. Object of the study was 20 patients under 5 years old who come to the community health center which diagnosed acute respiratory infection from April to May 2018. Measurement results in the location of community service showed that the lighting was 30% ineligible and the ventilation was 25% not qualified as well as a 100% number of germs air not qualified, due to physical environmental factors and community behavior itself. It was supported by the observations to the field that showed the behavior of the people in keeping the environment in the patient's room still inadequate. Inadequate behavior in this case was the behaviors of parents who did not close their mouth when sneezing with a handkerchief or tissue, which can of course worsen the air quality concerning the number of germs the air. Thus patients' environmental factors and behavior of the caregivers in the prevention of acute respiratory infection need to be improved by giving health education from the health workers of the health center and educational institutions related.Keywords: Home environment, Behavior, Acute respiratory infection